The Effect of Wearing A Mask on Oxygen Saturation and Pulse Rate During Climbing Stair in Public Areas - Jaya, I Putu Prisa; Astrawan, I Putu; Negara, Ni Luh Gede Aris Maytadewi; Empuaji, Made Ganggas Dwiatmaja (Indonesian Journal of Global Health Research, 2024)
The wearing of masks is one of the mitigation strategies in preventing transmission and is the main protective tool in the Covid-19 pandemic. The wearing of masks for a long duration and long period of time influences the respiratory, vision, and communication systems. Purpose: The purpose of this study was to determine the effect of wearing a mask on climbing stairs on physiological responses measured through oxygen saturation and pulse rate. Method: Experimental research with crossover design. The research was conducted at the Bali International University in June – August 2022. The research subjects in this study were employees and lecturers for 40 people. Results: Based on the results of the analysis with the t-independent test, there was a significant difference in oxygen saturation and pulse rate between the two groups. The same result was also obtained in period II, there was a difference in oxygen saturation and pulse rate between the two groups meaningfully, with a range of values that were not much different from the results in the activity of climbing the ladder of period I. Overall, there was a significant difference in oxygen saturation and pulse rate between wearing a mask and not wearing a mask. Conclusion: Based on the results of this study, it has a high impact on physiological response, so the elderly is not recommended to use masks when climbing stairs that exceed 2 floors.